2019
DOI: 10.1186/s41610-018-0101-4
|View full text |Cite
|
Sign up to set email alerts
|

C:N:P stoichiometry of particulate and dissolved organic matter in river waters and changes during decomposition

Abstract: Background: Stoichiometry plays an important role in understanding nutrient composition and cycling processes in aquatic ecosystems. Previous studies have considered C:N:P ratios constant for both DOM (dissolved organic matter) and POM (particulate organic matter). In this study, water samples were collected in the six major rivers in Korea and were incubated for 20 days. C:N:P ratios were determined during the time course of the incubations. This allowed us to examine the changes in N and P contents of organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
3
6
0
Order By: Relevance
“…Notably, no significant change occurred in the DON concentration during the biodegradation experiments at any of the six sites. DON generally degrades during incubation in the dark (Seitzinger and Sanders, 1997;Stepanauskas et al, 2000;Wiegner et al, 2009), and N-rich DOM is generally considered to be more biodegradable than C-rich DOM (Wiegner et al, 2006;Hendrickson et al, 2007;Petrone et al, 2009;Wiegner et al, 2009;Islam et al, 2019). In contrast, no change or increase in DON concentration was observed in several dark incubation experiments conducted previously (Kaushal and Lewis, 2005;Wiegner et al, 2006;Pisani et al, 2017), which was similar to the results of our dark incubation experiments (Figure 5).…”
Section: Bioavailability Of Don and Doc In The Riversupporting
confidence: 89%
See 2 more Smart Citations
“…Notably, no significant change occurred in the DON concentration during the biodegradation experiments at any of the six sites. DON generally degrades during incubation in the dark (Seitzinger and Sanders, 1997;Stepanauskas et al, 2000;Wiegner et al, 2009), and N-rich DOM is generally considered to be more biodegradable than C-rich DOM (Wiegner et al, 2006;Hendrickson et al, 2007;Petrone et al, 2009;Wiegner et al, 2009;Islam et al, 2019). In contrast, no change or increase in DON concentration was observed in several dark incubation experiments conducted previously (Kaushal and Lewis, 2005;Wiegner et al, 2006;Pisani et al, 2017), which was similar to the results of our dark incubation experiments (Figure 5).…”
Section: Bioavailability Of Don and Doc In The Riversupporting
confidence: 89%
“…Furthermore, Wiegner et al (2006) conducted a degradation experiment in rivers on the east coast of the United States at 25 °C under dark conditions for 6 days and observed that DON had a higher degradation rate and higher bioavailability than DOC. Similar results have been observed in different rivers (Hendrickson et al, 2007;Petrone et al, 2009;Wiegner et al, 2009;Islam et al, 2019). The contribution of protein-like fluorophores to total fluorophores has been related to the bioavailability of bulk DOM (Balcarczyk et al, 2009;Fellman et al, 2009;Petrone et al, 2011), implying that at least fractions of the DON, such as peptides and proteins, are actively involved in the metabolism of lower trophic levels in riverine ecosystems.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…As expected, in this study the absolute amounts of reactive organic matter (measured as BOD 5 ) in the merged data increased with bulk TOC, which is a proxy variable for colour in natural (Laudon, Köhler, & Buffam, 2004) The reactivity could to a certain extent be explained by the quality of the organic matter, as the low-TOC rivers with the highest k had the lowest organic C:N ratios, and vice versa. Organic matter with a low C:N ratio is highly biodegradable (Fellman et al, 2008;Islam et al, 2019), owing to its low contents of recalcitrant aromatic carbon rings (Hood, Williams, & McKnight, 2005), but high content of aliphatic and peptide-like structures (Kellerman et al, 2018;Spencer et al, 2019). High N contents of organic matter is common in agriculture-influenced rivers (Spencer et al, 2019) and typically originates from labile benthic algal and phytoplankton sources, whereas low N contents (high C:N) is linked to detritus from terrestrial sources (Balakrishna & Probst, 2005;Kaiser, Arscott, Tockner, & Sulzberger, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Though Li et al (2019) reported that corn stalk mulching increased DOC export from bare soils under simulated rainfall, there is no relevant study on the changes in DOC concentration of runoff water from cultivated fields under natural rainfall. The potentially increased DOC concentration should increase stoichiometric ratio of C to N (C/N) and C to P (C/P), which varies with land-use type and management (Yang et al, 2012;Islam et al, 2019). For example, Yang et al (2012) reported that C/N and C/P in soluble fractions of soil CNP varied from 2 to 8 and from 5 to 100, respectively, under different land-use type and management including field crop soils, pasture, and forests in Florida, USA.…”
Section: Introductionmentioning
confidence: 99%